A Reduced Series/Parallel Module for Cascade Multilevel Static Compensators Supporting Sensorless Balancing - Li Z.; Motwani J.K.; Zeng Z.; Lukic S.M.; Peterchev A.V.; Goetz S.M. (My University, 2025)
Cascaded multilevel converters have been gaining popularity in static compensators (STATCOMs) owing to their excellent modularity, output quality, and fault tolerance. However, cascaded multilevel converters require a large number of galvanically isolated voltage sensors and complex communication systems in order to balance the module dc-link voltages. This article proposes a reduced series/parallel module (RSPM) that intends to replace H-bridges in cascaded multilevel STATCOMs. Any adjacent RSPMs can be configured in series, bypass, or parallel. Cycling the parallel state through all modules balances all capacitor voltages in a sensorless manner. Since the RSPM-balancing process occurs at the hardware level, H-bridges can be easily replaced by RSPMs without changing higher-level control loops. Compared to existing series/parallel modules, the RSPM has the same functionalities but uses 25% fewer transistors. Despite the reduced switch count, the RSPM is shown to achieve even better efficiency under certain load conditions. The RSPM also attains similar semiconductor utilization ratio as H-bridge modules. The features of the RSPMs are verified on simulations and a down-scaled experimental setup. © 1982-2012 IEEE.